Does reviving organizations serve an advantage for college students? - Yayuk Hidayah; Meiwatizal Trihastuti; Lili Halimah; Dianasari Dianasari (Future Science, 2022)
Student organizations are very essentials in developing basic qualities of students and share interests, talents, and potential in extracurricular activities in the organizations. In Indonesia, student organizations play an important role of developing the student potential. The purpose of this article therefore is to review, describe, and explore the benefits of student organizations. Data were collected from eight Student Executive Board (BEM) in eight different campuses located in the Special Region of Yogyakarta. The phenomenological approach is carried out to uncover the usefulness of student organizations. In general, this article establishes that student organizations support the mastery of citizenship skills. The results show that there are 5 benefits students gain, including (1) Increasing civic awareness, (2) Increasing civic engagement, (3) enhanced the level of professionalism, (4) Instilling creativity, and (5) improved critical thinking. This article concludes that there is a need to carry out activities related to the management of skills in the planning work programs of the Student Executive Board (BEM), participating in scientific meetings, seminars, conferences, or training. This leads to a harmonious work atmosphere and wise decision making.